Navigated Recovery of Fractured Dental Injection Needles: Case Report and Suggestions for Management during Pandemic Crises - Lara Schorn; Christoph Sproll; Rita Depprich; Norbert R. Kübler; Majeed Rana; Daman D. Singh; Julian Lommen (Hindawi Limited, 2021)
Dislocation of a fractured hypodermic needle is a complication requiring immediate and adequate emergency treatment. In this case report, 3D navigation is evaluated for its use to recover a quickly moving fractured needle. The needle was recovered safely, but it could be demonstrated that navigational planning has to be conducted right before surgery and other navigational tools, such as ultrasound, should be considered as well. Furthermore, an approach is suggested for treatment during pandemic crises such as COVID-19.